The astroglial and stem cell functions of adult rat folliculostellate cells. Issue 2 (12th September 2022) - Fletcher, Patrick A.; Smiljanic, Kosara; Prévide, Rafael M.; Constantin, Stephanie; Sherman, Arthur S.; Coon, Steven L.; Stojilkovic, Stanko S.
Abstract: The mammalian pituitary gland is a complex organ consisting of hormone‐producing cells, anterior lobe folliculostellate cells (FSCs), posterior lobe pituicytes, vascular pericytes and endothelial cells, and Sox2 ‐expressing stem cells. We present single‐cell RNA sequencing and immunohistofluorescence analyses of pituitary cells of adult female rats with a focus on the transcriptomic profiles of nonhormonal cell types. Samples obtained from whole pituitaries and separated anterior and posterior lobe cells contained all expected pituitary resident cell types and lobe‐specific vascular cell subpopulations. FSCs and pituicytes expressed S100B, ALDOC, EAAT1, ALDH1A1, and VIM genes and proteins, as well as other astroglial marker genes, some common and some cell type‐specific. We also found that the SOX2 gene and protein were expressed in 15% of pituitary cells, including FSCs, pituicytes, and a fraction of hormone‐producing cells, arguing against its stem cell specificity. FSCs comprised two Sox2 ‐expressing subclusters; FS1 contained more cells but lower genetic diversity, while FS2 contained proliferative cells, shared genes with hormone‐producing cells, and expressed genes consistent with stem cell niche formation, regulation of cell proliferation and stem cell pluripotency, including the Hippo and Wnt pathways. FS1 cells were randomly distributed in the anterior and intermediate lobes, while FS2 cells were localized exclusively in the marginal zone between the anterior and intermediate lobes. These data indicate the identity of the FSCs as anterior pituitary‐specific astroglia, with FS1 cells representing differentiated cells equipped for classical FSC roles and FS2 cells exhibiting additional stem cell‐like features. Main Points: Pituitary folliculostellate cells (FSCs) were studied with scRNAseq and immunohistofluorescence. Expression profiles of FSCs and pituicytes confirmed their astroglial identity. FSC subtypes included pituitary stem‐like cells and differentiated FSCs.